PENGARUH JOB DESCRIPTION DAN JOB SPECIFICATION TERHADAP KINERJA PROSES - Salmah Pattisahusiwa (Faculty of Economics and Business Mulawarman University, 2013)
The purpose of this research explan the effects job description and job specification to performance of the process of the organization in an environment of local governments. A study in 2012 at the Organization of Kutai Kartanegara, East Kalimantan. Studies conducted a study of explanation (explanatory research) study/research that explains the causal relationship between the variables research through testing hypotheses. The Data collected from the respondent that the from various strata/echelon personnel taken 4 people are random in each (as much as 40) in the survey. Thus the total number of samples is 160 people. Data that has been collected is processed by the program Smart PLS 2.0. Research results show that understanding of the employees of the authority, responsibility, conditions of work, facilities, standards work, are able to improve the performance of the process in this case ability of employees in delivering Responsiveness, Accountability, Responsibilitas, survival, openness/transparency and. However, specification of terms (education and training as well as the competence of the employees) have not been able to improve the performance of the process (Responsiveness, Accountability, Responsibilitas, survival, openness/transparency, and empathy).Keywords : job description, job specification/, process performance